Fluorescence to multi-colored phosphorescence interconversion of a novel, asterisk-shaped luminogen via multiple external stimuli. Issue 31 (19th March 2020) - Jia, Xiaoyong; Yue, Bingbing; Zhou, Lulu; Niu, Xiling; Wu, Weiling; Zhu, Liangliang
Abstract : Photoluminescence from blue fluorescence to green, yellow, and orange phosphorescence can be switched via multiple stimuli on an asterisk-shaped compound. Abstract : We designed and characterized an asterisk-shaped luminogen, hexakis(pyridin-4-ylthio)benzene (HPTB). Via external stimuli such as CH3 OH, H +, and Ag +, HPTB's luminogenic character transitioned from blue fluorescence to green, yellow, and orange phosphorescence. Results showed that this interconversion was a reversible process that was also reproducible in liquid and in the solid state.